2016
DOI: 10.1177/2055217316631762
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variations of multiple sclerosis prevalence in France: The latitude gradient is not uniform depending on the socioeconomic status of the studied population

Abstract: BackgroundIn France, two studies analysed multiple sclerosis prevalence nationwide: one was carried out in farmers, and the other one in employees. A south-north gradient of prevalence was found solely in farmers.ObjectiveIn order to better describe the latitude gradient in France, which is not uniform depending on the studied population, we assessed whether a gradient exists in another population than farmers and employees: independent workers. The same methods of case ascertainment have been used.MethodsAlto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…That MS prevalence increases with greater distance from the equator led to the hypothesis that lower exposure to ultraviolet (UV) radiation and subsequently, lower vitamin D status (blood concentration of 25‐hydroxyvitamin D (25OHD)), increases the risk of MS. Latitude gradients have reduced over time in some populations, but not all; this may be due to changes in exposure to latitude‐related factors, for example, sun exposure, diet, in some populations, but not others. Higher latitude and lower summer sun exposure in adolescence have been linked to a younger age of onset.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…That MS prevalence increases with greater distance from the equator led to the hypothesis that lower exposure to ultraviolet (UV) radiation and subsequently, lower vitamin D status (blood concentration of 25‐hydroxyvitamin D (25OHD)), increases the risk of MS. Latitude gradients have reduced over time in some populations, but not all; this may be due to changes in exposure to latitude‐related factors, for example, sun exposure, diet, in some populations, but not others. Higher latitude and lower summer sun exposure in adolescence have been linked to a younger age of onset.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…Furthermore, the lowest prevalence was found in the departments of the Auvergne region, located in the center of France. Therefore, these results do not show a clear northeast to southwest gradient among the 21 departments under study, as was previously suggested in the 2003 national study of data for French farmers [3] and more recently among independent workers [19], but the results are closer to those in the 2004 national study of data for the main national health insurance system (CNAMTS) [13]. Moreover, the high prevalence in Haute-Garonne (SW) is consistent with the results obtained in the capture–recapture study conducted in Haute-Garonne in 2005 [15].…”
Section: Discussionmentioning
confidence: 49%
“…As compared with previous studies, these studies revealed increased prevalence in these five departments. More recently, a study of a population of independent workers that involved a Bayesian method found a decreasing northeast to southwest gradient on departmental scale [19]. …”
Section: Introductionmentioning
confidence: 99%
“…However, as a low Gini coefficient was found, the authors concluded that the causes of MS are pervasive and shared across population groups [ 6 ]. In French territory, several studies found geographic variations in MS but at much larger geographical scales than the municipality level ( département or region), highlighting higher prevalence or incidence rates in north-eastern France [ 8 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%